Potential Use of Lactobacillus plantarum 1UHCC as a Bio-hydrolyzer in the Development of the Sustainable Food Industry in Indonesia - Said, Muhammad Irfan; Abustam, Effendi; Nur Yuliati, Farida; Hasma, H.; Alvina, A. (European Journal of Sustainable Development, 2020)
The purpose of this study aimed to evaluate the potential and performance of Lactobacillus plantarum 1 UHCC (L.plantarum 1UHCC) bacteria as bio-hydrolyzer of the food industry in Indonesia. As much as 100g of fresh hide from Balinese cattle were used as a substrate. The fermentation time was carried out at 3 time levels, namely: 24 hours (T-24); 48 hours (T-48) and 72 hours (T-72). The bacteria were used L.plantarum which was isolated from milkfish extract. The results showed that in the solution of L.plantarum bacteria using collagen substrate of cattle hide, pH values were increased and the lactic acid levels were decreased significantly. The pH value and the lactic acid level of the solution were respectively around 5.77±0.03-6.13±0.02 and 1.65±0.26-2.02±0.05%. The total bacteria has increased and dissolved protein has decreased for fermentation time, but in general it is not significant. Total bacteria and dissolved proteins respectively 4.5±0.98-5.5±2.29 Log10CFU/mL and 36.98±3.37-40.25±1.54 mg/mL. The application of 24 hours (T-24) fermentation time to L.plantarum bacteria using collagen substrate of cattle hide skin was considered as the optimum time to be applied in the fermentation process. Bacteria L.plantarum 1UHCC has the ability to hydrolyze collagen protein components, especially collagen extracts from cattle hide. Bacteria L.plantarum 1UHCC has the potential to be developed as a bio-hydrolyzer organism. Bacteria L.plantarum 1UHCC plays a very important role in the development of the food industry, especially in Indonesia. Keywords: Bacteria, Cattle hide, Collagen, Fermentation, L.plantarum 1UHCC